(untitled) (Journal of Shaheed Suhrawardy Medical College, 2013)
Breast feeding by sucking is the norm. However sometimes expression is the only way by which breast milk can be given to babies. There are many situations when expressing breast milk is useful and necessary to enable a mother to initiate or to continue breast feeding. Hand or breast pump are used to express breast milk. Hand expression is the most preferred method. There are some mechanical pumps though pumps cause discomfort and are usually ineffective. The Marmet technique of expressing breast milk with hand is a fabulous alternative to using a breast pump. Until recently hand expression of breast milk has been as underutilized skill. However, there are many benefits of knowing how to express milk from the breast without the use of expensive and cumbersome breast pumps. Expressed breast milk can be feed by spoon, cup and nasogastric tube. It is essential to collect and store breast milk properly to prevent the risk of bacterial overgrowth. Feeding with breast milk is quite safe if done properly. It is important for every woman to learn to express the milk. Certainly all health workers who take care for breastfeeding mothers should be able to teach the way of expression of breast milk. DOI: http://dx.doi.org/10.3329/jssmc.v4i2.14422 J Shaheed Suhrawardy Med Coll, 2012;4(2):62-64